2017
DOI: 10.1108/intr-09-2016-0258
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of online retailers’ micro-blogs on consumers’ purchase intention

Abstract: Purpose The purpose of this paper is to identify the key determinants of the information value of enterprises’ micro-blogs, drawing on the consumer’s perspective. This paper examines the effects of such information value on consumers’ purchase intention through the building of online brand equity. The paper also investigates how perceived usefulness intervenes in the relationship between micro-blog information value and consumer purchase intention. Design/methodology/approach The proposed research model is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Consumers tend to rely on WOM to reduce the level of perceived risk and uncertainty (Klein, 1998). In the internet era, the effects and distribution of WOM have been further enhanced since personal recommendations are made massively available on an impersonal basis (Zhou et al , 2017). Yet, the impersonal nature of the information provided does not appear to have impacted negatively on its potential use by others in the tourism domain.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…Consumers tend to rely on WOM to reduce the level of perceived risk and uncertainty (Klein, 1998). In the internet era, the effects and distribution of WOM have been further enhanced since personal recommendations are made massively available on an impersonal basis (Zhou et al , 2017). Yet, the impersonal nature of the information provided does not appear to have impacted negatively on its potential use by others in the tourism domain.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…Timely content that is up-to-date creates a positive online experience by giving users context and relevant information (Chowdhry, 2018;De Choudhury et al, 2011), which in turn communicates value-added information (Cheung et al, 2008). For instance, Zhou et al (2017) analyzed online retailers' microblog posts and their influence on purchase intention to determine that timely, pertinent and thorough information about a firm's products or services aids consumers decisions. A fairly recent survey revealed that consumers follow brands on SMPs to keep up with trends (Chahal, 2016), whereas Lim and Kumar's (2019) study found that timeliness and new updates are important motives that drive consumers to use Facebook brand pages.…”
Section: Effects Of Content Quality On Flow Experiencementioning
confidence: 99%
“…Consumers' fundamental shopping orientations have no significant impact on their proclivity to purchase products online. Factors that are more likely to influence purchase intention include prior purchase, product type, and gender (Zhou et al, 2017;Brown et al, 2003).…”
Section: Review Of Literaturementioning
confidence: 99%